LAND LAW, LAND RELATIONS AND ISSUES OF LAND SURVEY IN HISTORICAL ARMENIA BY WORKS OF S. BAHATREANTS AND H. MUSAELYAN (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
Studies of land relations, land law and land survey issues in different eras in Armenia are now more relevant and important than ever. Armenian nakharars, meliks and even peasants for many centuries basically preserved the lands they owned, land titles (in particular, the right of inheritance) and forms of land tenure even during the times of foreign conquests and loss of statehood. The paper focuses on these particular objectives. The presented sources are investigated for the first time from the point of view of land law, land relations, and the history of land management.
Keywords: land law; land relations; land management; history of land management; land survey